Pineapple Leaves (Ananas Comosus) Ca-Alginate Immobilized as Adsorbent For Removal of Rhodamine B Dye - Intan Lestari; Nelson Nelson; Damris M; Najlia Dinnisa Syawabilla (CHEMICA: Jurnal Teknik Kimia, 2023)
Rhodamine B dye is one of the dye wastes from the textile dyeing industry. One way that can be done for dealing with pollution of the aquatic environment by the presence of this dye is adsorption. This study aims to adsorption of Rho B dye using Ca-alginate immobilized pineapple leaves. Immobilization of pineapple leaves with alginate aims to improve adsorbent performance, mechanical strength, and adsorption capacity. Pine apple leaf Ca-alginate immobilized adsorbents were characterized using Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), and X-Ray Fluorescence (XRF) instruments. Ca-alginate immobilized pineapple leaf adsorbent was used adsorption of Rho B dye by studying several adsorption parameters such as the effect of pH, contact time, mass of adsorbent, stirring speed, and concentration of Rho B dye. The optimum adsorption conditions parameters were obtained at pH 3, contact time during 90 minutes, agitation speed of 150 rpm, the adsorbent mass of 0.1 gram, and Rho B concentration of 80 mg/L with a maximum adsorption capacity of 8.964 mg/g.